How Politics Shape Views Toward Fact-Checking: Evidence from Six European Countries. (July 2020) - Lyons, Ben; Mérola, Vittorio; Reifler, Jason; Stoeckel, Florian
Fact-checking has spread internationally, in part to confront the rise of digital disinformation campaigns. American studies suggests ideological asymmetry in attitudes toward fact-checking, as well as greater acceptance of the practice among those more interested in and knowledgeable about politics. We examine attitudes toward fact-checking across six European counties to put these findings in a broader context ( N  = 6, 067). We find greater familiarity with and acceptance of fact-checking in Northern Europe (Sweden and Germany) than elsewhere (Italy, Spain, France, and Poland). We further find two dimensions of political antipathy: a left–right dimension and an "anti-elite" dimension (including dissatisfaction with democracy and negative feelings toward the European Union), the latter of which more consistently predicts negative feelings toward fact-checkers in the countries examined. Our findings demonstrate that despite general acceptance of the movement, significant political divides remain. Those less likely to trust fact-checkers could be more vulnerable to disinformation targeting these divides, leading to a spiral of cynicism.